The Role of Clinical Pharmacist in Reducing Drug Related Problems in Hemodialysis Patients - Talib, Aya F.; M.Anwer, Zinah (Iraqi Journal of Pharmaceutical Sciences, 2020)
Abstract Prescribing drugs to patients to treat ailments or reducing their morbidity may not be enough, even if the drugs were all indicated and in the right dose. Clinical pharmacists play a pivotal role in conducting information and instruction to patients and conveying feedback to treating physician when appropriate, and the final goal is in the interest of the patient. Identification and classification of drug related problems and discussing them with the health care providers. Prospective, interventional, clinical study for 180 hemodialysis patients, and was designed as two phases, an observational phase to identify drug related problems and classifying them according to the latest Pharmaceutical Care Network Europe classification, an interventional phase to increase the awareness of patients and the nephrologists about those problems and proposing a proper solution for each one. The main drug related problems was related to the effect of drug treatment being not optimal in 58.7%, followed by no effect in 17.8%, and least for unrelated symptoms or indications in 4.8%; causes were inappropriate combination and patients taking less drug than prescribed (both 17.4%), followed by no/or incomplete drug treatment in spite of existing indication in 12.2%, drug without indication in 10.4%. Erythropoietin and calcium were the most frequently drugs with problems. Acceptance and full implementation were observed in 34.3%, while half of the drug related problems had unknown implementation (51.3%). There were significant numbers of drug related problems among Iraqi patients on hemodialysis, the use of erythropoietin, calcium carbonate and sevelamer was responsible for most of inappropriate combinations. Physicians and clinical pharmacist cooperation was excellent. Keywords: Drug related problems, Hemodialysis, Clinical pharmacist.